2019
DOI: 10.1029/2018gl081132
|View full text |Cite
|
Sign up to set email alerts
|

Premonsoon/Postmonsoon Bay of Bengal Tropical Cyclones Intensity: Role of Air‐Sea Coupling and Large‐Scale Background State

Abstract: The densely populated Bay of Bengal (BoB) rim witnesses the deadliest tropical cyclones (TCs) globally, before and after the summer monsoon. Previous studies indicated that enhanced salinity and reduced thermal stratification reduce cooling under BoB TCs after the monsoon, suggesting that air‐sea coupling may favor stronger TCs during that season. Using observations and simulations from a one fourth degree regional ocean‐atmosphere model, we show that BoB TCs are stronger before the monsoon due to a more favor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 63 publications
0
20
0
Order By: Relevance
“…This high productivity, together with low ventilation, leads to a subsurface depletion of oxygen (oxygen minimum zone, OMZ) that is now expanding and has already led to a dramatic shift in the Arabian Sea and Bay of Bengal ecosystem (Gomes et al, 2014;Bristow et al, 2017). Excess freshwater input from monsoon rain and river runoff generates strong saline stratification in the Bay of Bengal, inhibiting mixing and influencing oceanic productivity (Prasanna Kumar et al, 2002) and sea surface temperature (SST), which in turn regulate regional climate (Shenoi et al, 2002) and weather extremes (Neetu et al, 2019).…”
mentioning
confidence: 99%
“…This high productivity, together with low ventilation, leads to a subsurface depletion of oxygen (oxygen minimum zone, OMZ) that is now expanding and has already led to a dramatic shift in the Arabian Sea and Bay of Bengal ecosystem (Gomes et al, 2014;Bristow et al, 2017). Excess freshwater input from monsoon rain and river runoff generates strong saline stratification in the Bay of Bengal, inhibiting mixing and influencing oceanic productivity (Prasanna Kumar et al, 2002) and sea surface temperature (SST), which in turn regulate regional climate (Shenoi et al, 2002) and weather extremes (Neetu et al, 2019).…”
mentioning
confidence: 99%
“…At seasonal timescales, these data demonstrated that thick barrier layers are induced by stronger haline stratification and a deeper thermocline after the monsoon (Thadathil et al 2016). These thick barrier layers contribute to much weaker TC-induced cooling as compared to the pre-monsoon period (Neetu et al 2012(Neetu et al , 2019, fostering post-monsoon TC intensification (Balaguru et al 2012). Similarly, the SCTR is one of the rare oceanic regions where warm SSTs coexist with a shallow thermocline, which can enhance cooling under a TC.…”
Section: Extreme Eventsmentioning
confidence: 99%
“…While TCs primarily arise from atmospheric processes, they are nonetheless strongly influenced by ocean-atmosphere interactions. The SST cooling under TCs (Vincent et al 2012;Neetu et al 2012) indeed reduces the total enthalpy flux to the atmosphere and hence limits the cyclone intensification (Lengaigne et al 2018;Neetu et al 2019). Ocean-atmosphere interactions may therefore modulate climate variability over a wide range of time and spatial scales and must hence be carefully monitored.…”
Section: Actionable Recommendationsmentioning
confidence: 99%
“…3c). By inhibiting vertical mixing of heat, nutrients, and oxygen this salinity stratification is thought to favor warmer SSTs, which promote monsoon rainfall (Shenoi et al 2002) and more intense cyclones (Sengupta et al 2008;Neetu et al 2019), to reduce oceanic productivity (Prasanna Kumar et al 2002), and to lead to an OMZ in the Bay of Bengal (Sarma et al 2016). The annual-mean westerly winds along the equator in the Indian Ocean damp the equatorial upwelling that is found to the east of other tropical oceans.…”
Section: The Indoos Reviewmentioning
confidence: 99%